Pengaruh Kualitas Pelayanan Ritel dan Atmosfir Gerai Terhadap Loyalitas Pelanggan Pada Mini Market Bina Karya - Andayani Andayani; Ronda Deli Sianturi (Journal of Business and Economics Research (JBE), 2021)
This study consists of three variables, namely, retail service quality variable (X1), store atmosphere (X2), and customer loyalty (Y). In general, the purpose of this study was to determine the effect of retail service quality and outlet atmosphere on customer loyalty at the Bina Karya Minimarket. The method used in this research is descriptive and associative method. In this study obtained a sample of 96 people. Data collection techniques used in this study were library research, questionnaires, interviews, and documentation studies. The data measurement scale used in this study is an interval scale. The data obtained from the questionnaire results were then processed using validity test, reliability test, t test, correlation coefficient analysis, and coefficient of determination and multiple regression analysis. Based on the results of research from multiple regression calculations, the results obtained which state that partially the quality of retail services and the atmosphere of the outlets affect customer loyalty so that H0 is rejected, meaning that the quality of retail services and the atmosphere of the outlets affect customer loyalty.